Evidence for a Role of the Lateral Ectoderm in Drosophila Mesoderm Invagination - Guo, Hanqing; Huang, Shicheng; He, Bing (Frontiers in Cell and Developmental Biology, 2022)
The folding of two-dimensional epithelial sheets into specific three-dimensional structures is a fundamental tissue construction mechanism in animal development. A common mechanism that mediates epithelial folding is apical constriction, the active shrinking of cell apices driven by actomyosin contractions. It remains unclear whether cells outside of the constriction domain also contribute to folding. During Drosophila mesoderm invagination, ventrally localized mesoderm epithelium undergoes apical constriction and subsequently folds into a furrow. While the critical role of apical constriction in ventral furrow formation has been well demonstrated, it remains unclear whether, and if so, how the laterally localized ectodermal tissue adjacent to the mesoderm contributes to furrow invagination. In this study, we combine experimental and computational approaches to test the potential function of the ectoderm in mesoderm invagination. Through laser-mediated, targeted disruption of cell formation prior to gastrulation, we found that the presence of intact lateral ectoderm is important for the effective transition between apical constriction and furrow invagination in the mesoderm. In addition, using a laser-ablation approach widely used for probing tissue tension, we found that the lateral ectodermal tissues exhibit signatures of tissue compression when ablation was performed shortly before the onset of mesoderm invagination. These observations led to the hypothesis that in-plane compression from the surrounding ectoderm facilitates mesoderm invagination by triggering buckling of the mesoderm epithelium. In support of this notion, we show that the dynamics of tissue flow during mesoderm invagination displays characteristic of elastic buckling, and this tissue dynamics can be recapitulated by combining local apical constriction and global compression in a simulated elastic monolayer. We propose that Drosophila mesoderm invagination is achieved through epithelial buckling jointed mediated by apical constriction in the mesoderm and compression from the neighboring ectoderm.